The asbestos–asbestosis exposure–response relationship: a cohort study of the general working population - Iversen, Inge Brosbøl; Vestergaard, Jesper Medom; Ohlander, Johan; Peters, Susan; Bendstrup, Elisabeth; Bonde, Jens Peter E; Schlünssen, Vivi; Bønløkke, Jakob Hjort; Rasmussen, Finn; Stokholm, Zara A; Andersen, Michael B; Kromhout, Hans; et al. (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVES ': 'The association between asbestos exposure and asbestosis in high-exposed industrial cohorts is well-known, but there is a lack of knowledge about the exposure–response relationship for asbestosis in a general working population setting. We examined the exposure–response relationship between occupational asbestos exposure and asbestosis in asbestos-exposed workers of the Danish general working population. ' ' METHODS ': 'We followed all asbestos-exposed workers from 1979 to 2015 and identified incident cases of asbestosis using the Danish National Patient Register. Individual asbestos exposure was estimated with a quantitative job exposure matrix (SYN-JEM) from 1976 onwards and back-extrapolated to age 16 for those exposed in 1976. Exposure–response relations for cumulative exposure and other exposure metrics were analyzed using a discrete time hazard model and adjusted for potential confounders. ' ' RESULTS ': 'The range of cumulative exposure in the population was 0.001 to 18 fibers per milliliter-year (f/ml-year). We found increasing incidence rate ratios (IRR) of asbestosis with increasing cumulative asbestos exposure with a fully adjusted IRR per 1 f/ml-years of 1.18 [95% confidence interval (CI) 1.15– -1.22]. The IRR was 1.94 (95% CI 1.53–2.47) in the highest compared to the lowest exposure tertile. We similarly observed increasing risk with increasing cumulative exposure in the inception population. ' ' CONCLUSIONS ': 'This study found exposure–response relations between cumulative asbestos exposure and incident asbestosis in the Danish general working population with mainly low-level exposed occupations, but there is some uncertainty regarding the exposure levels.
Keywords: asbestos; asbestosis; cohort study; exposure; exposure–response; interstitial lung disease; job exposure matrix; occupational exposure; register study; working population